Teaching ESP: The English Lecturers' Communicative Activities in Business English Instructions - MUSDARIAH, Andi; AMANSYAH, Farida (Politeknik Negeri Ujung Pandang, 2023)
This corrigendum article focuses on enhancing the communicative competence of ESP learners using a wide range of tasks or activities. The target audience for this article is students enrolled in the Business Administration program at the State Polytechnic of Ujung Pandang. By carefully designing activities based on each student’s level and the standards they must meet, we facilitated them to connect with their classmates in the classroom and improve their speaking ability. The purpose of this study was to demonstrate that students can improve their speaking skills by actively participating in the communicative activities that take place in the classroom. It was found that students were engaged in the activities and using the language when interacting with others in discussion sessions, group projects, and role-playing activities.